Food poisoning causes and prevention and what to know about hygiene - Roshed, Md Mamunur (PT Inovasi Pratama Internasional, 2024)
Food-borne diseases are the most common health problems globally, and they are particularly common in Third World countries like India due to poor public sanitation and hygiene. Broadly speaking, food poisoning refers to any illness brought on by eating food that contains bacteria or non-bacterial substances. Stated differently, it's an acute instance of gastroenteritis caused by ingesting chemicals-contaminated food or drink, animal or plant-derived poisons, or living microbes and their toxins. Acute gastroenteritis is one of the leading causes of morbidity and mortality. The most vulnerable are newborns and young children. The clinical symptoms of a foodborne infection are determined by the pathogenic mechanisms that underlie it. The main symptoms are headache, nervousness, intense thirst, abrupt vomiting, diarrhea, colicky discomfort, cold, clammy skin, slow heartbeat, rigours, and cramps. The provision of clean, drinkable water, appropriate disposal of human and animal sewage with isolation from water supplies, and fundamental food hygiene standards are all very effective ways to prevent the development of these disorders.